The Role Of The Teacher Professional Organization (PGRI) In Protecting Teacher Profession Disputes - Nuraini; Nurkolis (AJIS: Academic Journal of Islamic Studies, 2025)
This study examines the role of the Indonesian Teachers Association (PGRI) in protecting the professional rights of teachers involved in professional disputes at SD Negeri 2 Dadapan, Rembang Regency. The research was conducted using a qualitative approach, with data collected through interviews, observations, and documentation. The findings revealed that teachers at SD Negeri 2 Dadapan often face professional disputes, including conflicts with school principals, unilateral termination of employment, accusations of ethical violations without sufficient evidence, and criminalisation of teachers for disciplining students. The PGRI plays a significant role in providing legal assistance and advocacy, offering mediation services, and helping to resolve disputes through legal means. However, despite the efforts, challenges persist in implementing legal protections for teachers, mainly due to limited resources and a lack of coordination between PGRI and other related parties. This study highlights the importance of PGRI safeguarding teachers' professional rights. It suggests improvements in the organisation's capacity, mediation strategies, and coordination with government agencies for more effective protection of teachers' rights.